2020
DOI: 10.1111/ppc.12501
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for postpartum posttraumatic stress disorder and depression

Abstract: Purpose: In this study, we examined the association between specific birth-related variables and postpartum posttraumatic stress disorder (PTSD) and depressive symptoms. Design and Methods: In this descriptive study, data were collected using a personal information form, the City Birth Trauma Scale, and the Edinburgh Postpartum Depression Scale. Findings: The findings revealed that 8.5% of participants met all the diagnostic criteria for PTSD. The risk of developing depression was 9.7 times higher among women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
2
21
1
2
Order By: Relevance
“…This is consistent with other studies that have shown an association between traumatic birth experience and PPD 20,21 . A study conducted in Turkey found that the risk of developing PPD was higher in women with perceived birth trauma 22 . Literature report how women with perceived birth trauma may display more negative responses towards their children 23 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with other studies that have shown an association between traumatic birth experience and PPD 20,21 . A study conducted in Turkey found that the risk of developing PPD was higher in women with perceived birth trauma 22 . Literature report how women with perceived birth trauma may display more negative responses towards their children 23 .…”
Section: Discussionsupporting
confidence: 90%
“…PPD is consistently associated with poorer mother‐infant bond and mother‐infant interactions, 25 which may contribute to depression among women with perceived birth trauma. Furthermore, women with perceived birth trauma experienced more psychological stresses and had more negative emotions, resulting in relationship difficulties with their partners and other social interactions 22 . Such relationship stresses may be another contributing factor for the high prevalence of PPD in women with perceived birth trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PPD, postpartum post-traumatic stress disorder (PP-PTSD), a more severe mental disorder, has gained increased attention from researchers and clinicians worldwide [2]. High co-morbid rates of PPD and PP-PTSD have been reported by some researchers (90.4% of women with PP-PTSD had also experienced PPD and 31.5% women with PPD had also experienced PP-PTSD [2,9]. PP-PTSD is an anxiety disorder that develops as a direct consequence of a difficult or traumatic birth.…”
Section: Introductionmentioning
confidence: 99%
“…A traumatic childbirth experience can adversely affect a woman’s self-identity, self-efficacy, self-esteem, and mental health (Beck, 2004b; Bryanton et al, 2008). A recent study involving a Turkish population revealed that 8.5% of their mothers presented with all symptoms of post-traumatic stress disorder (PTSD) following traumatic childbirths (Bayri Bingol & Demirgoz Bal, 2020). A study among Australian mothers reported that 45.5% of mothers developed symptoms of PTSD 4–6 weeks after traumatic birth events (Alcorn et al, 2010).…”
mentioning
confidence: 99%